Regional Food Security Policy Directions to Ensure Adequate Food Availability and Access - Ariany, Lies; Zulaeha, Mulyani; Fahlani, Soffyan Angga; Mustika, Cindyva Thalia; Lestari, Saskia Dinda; Maulida, Eprilia; Andray, Nabil Noor (International Journal of Law, Environment, and Natural Resources, 2025)
Food security reflects the extent to which a country or region is capable of providing sufficient, safe, and nutritious food for its entire population. Efforts to strengthen food security are of vital importance in realizing a safe, healthy, and prosperous society. In the context of national development, food security has become one of the main priorities, which undoubtedly requires active support from local governments. This is closely related to the fulfilment of the right to food, which is a fundamental right of every citizen. The issue addressed in this study concerns the forms of food governance implemented by local governments to support food security at the local level. To address this issue, a normative legal research method is employed to examine the policy directions of local governments in ensuring the availability of food that is both adequate and accessible to the community. In ensuring the sustainable fulfilment of food needs, local governments play a strategic role in managing the food system within their regions. This role is realized through policy formulation, regulatory development, and the implementation of programs based on local potential. Thus, local governments can serve as key actors in promoting equitable and sustainable national food security.